Typically real logharmonic mappings - Zayid Abdulhadi (International Journal of Mathematics and Mathematical Sciences)
We consider logharmonic mappings of the form f(z)=z|z| 2βhg¯ defined on the unit disk U which are typically real. We obtain representation theorems and distortion theorems. We determine the radius of univalence and starlikeness of these mappings. Moreover, we derive a geometric characterization of such mappings.